The sacred Mahakala in the Hindu and Buddhist texts - Rana, Poonam R L (Nepalese Culture, 2019)
Mahakala is the God of Time, Maya, Creation, Destruction and Power. He is affiliated with Lord Shiva. His abode is the cremation grounds and has four arms and three eyes, sitting on five corpse. He holds trident, drum, sword and hammer. He rubs ashes from the cremation ground. He is surrounded by vultures and jackals. His consort is Kali. Both together personify time and destructive powers. The paper deals with Sacred Mahakala and it mentions legends, tales, myths in Hindus and Buddhist texts. It includes various types, forms and iconographic features of Mahakalas. This research concludes that sacred Mahakala is of great significance to both the Buddhist and the Hindus alike.